1983
DOI: 10.1080/00222216.1983.11969562
|View full text |Cite
|
Sign up to set email alerts
|

A Test of Concepts Inherent in Experience Based Setting Management for Outdoor Recreation Areas

Abstract: A B S T R A C T :This study examines assumptions o f the concepts which form the basis fo r experience based setting management o f outdoor recreation areas. To test the assumptions a sample o f wilderness users was surveyed and divided into experience groups based on differences in the specific experiences they desire. These experience groups were then tested fo r differences in their activity and setting preferences. The study was conducted at the Bridget Wilderness, the Fitzpatrick Wilderness, and the Popo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(38 citation statements)
references
References 8 publications
0
36
1
1
Order By: Relevance
“…It uses a four-point Likert scale to measure various responses of the questionnaire. For the benefits of local development part, we refer to [62,63]; for recreation experience benefit we refer to [64,65]; for festive identity, we referred to [48,52]; for festival support, we refer to [25,59,66].…”
Section: Methodsmentioning
confidence: 99%
“…It uses a four-point Likert scale to measure various responses of the questionnaire. For the benefits of local development part, we refer to [62,63]; for recreation experience benefit we refer to [64,65]; for festive identity, we referred to [48,52]; for festival support, we refer to [25,59,66].…”
Section: Methodsmentioning
confidence: 99%
“…More specifically, ROS is conceptualized as a four-tiered framework that links activities, settings, motivations, and benefits. The basis for this system is often described as "experience based setting management" (Floyd & Gramann, 1997;Manfredo, Driver, & Brown, 1983), and may be thought of as a type of "production process". It theorizes that experiences are derived from recreation activities, and that these activities are linked to the settings in which they occur.…”
Section: Ros Conceptmentioning
confidence: 99%
“…He suggested that people select a specific activity based on previous experiences with and in that activity. Manfredo et al (1983) agreed that motivation is driven by expectations. The authors hypothesized two specific types of expectations that include (a) an attempt to participate in a leisure activity that will eventually provide specific experiences (e.g., performances) and (b) these experiences as a means to achieve positive outcomes or desired states.…”
Section: Leisure Motivation Theoriesmentioning
confidence: 99%
“…Although there is a variety of magazine and online articles that discuss subjects related to females and surfing, there is little research in leisure literature focusing on why women choose to participate in the predominately male activity of surfing. Moreover, past research related to recreation specialization (Bryan, 1977(Bryan, , 1979Bricker & Kerstetter, 2000;Cameron, Schneider, Thompson, & Virden, 2003;Chipman & Helfrich, 1988;McIntyre, & Pigram, 1992;Miller & Graefe, 2000;Wellman et al, 1982) and motivations (Driver, 1976;Hase, 1996;Knopf, Peterson, & Leatherberry, 1983;Manfredo, Driver, & Brown, 1983;Manfredo et al, 1996) have typically used male subjects.…”
Section: Statement Of Problemmentioning
confidence: 99%
See 1 more Smart Citation